A new perspective on the third-country effect: The case of Malaysia–US industry-level trade. Issue 6 (18th August 2018) - Bahmani-Oskooee, Mohsen; Aftab, Muhammad
ABSTRACT: Cushman suggested that impact of exchange rate volatility declines after the inclusion of the third-country effect. Like Cushman, when we use a linear analysis, we confirm his results. However, when we engage in asymmetric effects of exchange rate volatility which requires including nonlinear adjustment of volatility measures, the findings show more support to both exchange rate volatility influence and the third-country effect. Therefore, we propose that in examining exchange rate volatility effect on trade, consideration must be given to not just asymmetric effects of exchange rate volatility but also asymmetric effects of the third-country effect. We demonstrate these findings using monthly data from 54 Malaysian industries that export to the US and 63 Malaysian industries that import from the US.